Contact-implicit preference relationships: Two large sample tests. Issue 5 (3rd September 2021) - Aberson, Christopher L.
ABSTRACT: This work examines relationships between friendships and implicit preferences across two large samples. There is considerable evidence in the contact literature suggesting that friendships relate to more favorable attitudes toward outgroups, however, most evidence reflects explicit self-report measures. Using samples of 235, 543 participants who completed the Disability IAT and 533, 220 participants who completed the Sexuality IAT on the Project Implicit website, results indicate that participants reporting either a disabled friend or close acquaintance demonstrated weaker implicit preferences for abled over disabled people. Similarly, those with gay friends demonstrated weaker implicit preference for "straight" over gay. The size of these relationships were considerably smaller than found for explicit evaluations. These effect size estimates should be useful to researchers studying contact-implicit preference relationships as it informs power analyses and sample size planning decisions.